"I don't know but I know who to ask": 12‐month‐olds actively seek information from knowledgeable adults. Issue 5 (26th February 2020) - Bazhydai, Marina; Westermann, Gert; Parise, Eugenio
Abstract: Active social communication is an effective way for infants to learn about the world. Do pre‐verbal and pre‐pointing infants seek epistemic information from their social partners when motivated to obtain information they cannot discover independently? The present study investigated whether 12‐month‐olds ( N = 30) selectively seek information from knowledgeable adults in situations of referential uncertainty. In a live experiment, infants were introduced to two unfamiliar adults, an Informant (reliably labeling objects) and a Non‐Informant (equally socially engaging, but ignorant about object labels). At test, infants were asked to make an impossible choice—locate a novel referent among two novel objects. When facing epistemic uncertainty—but not at other phases of the procedure—infants selectively referred to the Informant rather than the Non‐Informant. These results show that pre‐verbal infants use social referencing to actively and selectively seek information from social partners as part of their interrogative communicative toolkit. A video abstract of this article can be viewed at https://youtu.be/23dLPsa-fAY Abstract : Pre‐verbal infants used social referencing to actively and selectively seek information from social partners as part of their interrogative communicative toolkit. When facing referential uncertainty, but not during other phases of the procedure 12‐month‐old infants were more likely to reference the more knowledgeable person rather than the non‐informative person.